Monitoring the effectiveness of English as medium of instruction training provision for university research and teaching staff; 12th International Technology, Education and Development Conference (INTED2018) - Page M. Mary; Slesarenko I. V. Inga Valerievna; Francuzskaya E. O. Evgeniya Olegovna; Golubeva V. V. Vera Valerievna; Osokin G. E. Georgy Evgenievich; Fedorova N. A. Nataliya Alekseevna; Deeva V. S. Vera Stepanovna (2018, 2018)
Title screen